The Impact of Service Quality and Health Awareness on Customer Satisfaction and Loyalty: A Study on Perumda Tugu Tirta - Rofiaty , Rofiaty; Hidayatinnisa, Nurul (Jurnal Ilmiah Manajemen & Bisnis, 2024)
This study aims to determine and analyze the effect of service quality and health awareness of drinking water products on customer satisfaction and loyalty at Perumda Air Minum Tugu Tirta, Malang City, in 2024. The novelty of this research lies in the measurement of service quality through indicators such as: requirements, system mechanisms and procedures, completion time, costs/tariffs, product specifications, types of services, executor competence, executor behavior, handling of complaints, suggestions and feedback, facilities and infrastructure, product quality, and distribution. Additionally, the novelty of this study is the inclusion of customer health awareness as an independent variable. The population consists of all customers, with a sample of 400 customers who are making payments at the counters of the Perumda Tugu Tirta office in Malang City. This sample was chosen because customers can directly assess the quality of service. The results show that service quality can increase customer satisfaction and loyalty, while health awareness does not significantly affect customer satisfaction and loyalty. Customer satisfaction mediates the effect of service quality on customer loyalty but does not mediate the effect of health awareness on customer loyalty. The impact of service quality on customer satisfaction is significant, even through the mediation of health awareness. The findings indicate that customer behavior in consuming clean water does not prioritize health awareness, as customers rely on the fact that Perumda Tugu Tirta Malang City has received halal certification from the Indonesian Ulema Council (MUI) as well as certifications from the Ministry of Health. The results of this study offer valuable insights and suggestions for service improvements for the company and provide solutions to issues raised by customer complaints. Thus, the findings can serve as guidelines for future policy decisions. Keywords: Service Quality, Customer Awareness of Health, Satisfaction and, Customer Loyalty.